1993
DOI: 10.1007/bf00183942
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons among external resistive loading, drug-induced bronchospasm, and dense gas breathing in cats: Roles of vagal and spinal afferents

Abstract: In anesthetized cats, breathing spontaneously, increase in lung resistance (RL) was induced by either external resistive loads (ERL) or internal loading produced by dense gas breathing (sulfur hexafluoride, SF6) or serotonin (5-HT)-induced bronchoconstriction. The 3 test agents were used in each animal. Arterial blood gases were maintained in the normal range. Ventilatory and cardiovascular responses were studied in 3 groups of animals: intact, vagotomized, or spinalized at C8 level, a condition that preserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Both vagal and diaphragmatic afferents appear to play a crucial function in the integrative response to expiratory loads (35). In contrast, upper airway mechanoreceptors and corresponding afferent projections are not important contributors to the ventilatory response (36).…”
Section: Discussionmentioning
confidence: 99%
“…Both vagal and diaphragmatic afferents appear to play a crucial function in the integrative response to expiratory loads (35). In contrast, upper airway mechanoreceptors and corresponding afferent projections are not important contributors to the ventilatory response (36).…”
Section: Discussionmentioning
confidence: 99%
“…Sensory afferents from lung and airway could potentially contribute to resistive load compensation. There are studies, suggesting that stimulation of vagal bronchopulmonary afferents are involved in regulating the ventilatory responses to bronchoconstriction [ 11 ], as well as to external and internal (SF 6 -O 2 breathing) resistive loading [ 12 , 13 ]. We showed that substitution of air by He-O 2 or SF 6 -O 2 during exercise was accompanied by immediate changes in the volume-time values of the respiratory cycle, which is possibly related with the pulmonary stretch receptors activity.…”
Section: Discussionmentioning
confidence: 99%
“…The bronchopulmonary vagal C fibres are also stimulated by the marked variations in the airway pressure produced by breathing against an expiratory load [10]. An internal load produced by histamine-, serotonine-or cholinergic-induced bronchospasm or dense gas breathing also markedly activates the pulmonary vagal afferents [11,12].…”
Section: Lower Airway Afferentsmentioning
confidence: 98%